2022
DOI: 10.1038/s41380-022-01924-w
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and cognition in severe mental illness: patterns of covariation and subgroups

Abstract: A potential relationship between dysregulation of immune/inflammatory pathways and cognitive impairment has been suggested in severe mental illnesses (SMI), such as schizophrenia (SZ) and bipolar (BD) spectrum disorders. However, multivariate relationships between peripheral inflammatory/immune-related markers and cognitive domains are unclear, and many studies do not account for inter-individual variance in both cognitive functioning and inflammatory/immune status. This study aimed to investigate covariance p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 103 publications
3
10
0
Order By: Relevance
“…Based on covariance patterns in our main sample we identified a more compromised low cognition – high inflammatory-immune dysregulation subgroup, consisting primarily of individuals with SMI. This is a consistent pattern also observed in our previous work using a different inflammatory-immune marker panel (Sæther et al, 2023), and is in line with evidence that individuals with SMI in high inflammatory subgroups tend to have lower cognitive functioning (Fillman et al, 2016; Lizano et al, 2023a, 2020). We also found that individuals with SMI with co-occurring inflammation and cognitive impairment have more symptoms and lower functioning, which may be important to consider in future clinical trials.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Based on covariance patterns in our main sample we identified a more compromised low cognition – high inflammatory-immune dysregulation subgroup, consisting primarily of individuals with SMI. This is a consistent pattern also observed in our previous work using a different inflammatory-immune marker panel (Sæther et al, 2023), and is in line with evidence that individuals with SMI in high inflammatory subgroups tend to have lower cognitive functioning (Fillman et al, 2016; Lizano et al, 2023a, 2020). We also found that individuals with SMI with co-occurring inflammation and cognitive impairment have more symptoms and lower functioning, which may be important to consider in future clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that individuals with SMI with co-occurring inflammation and cognitive impairment have more symptoms and lower functioning, which may be important to consider in future clinical trials. Interestingly, we found the same cognitive domains as in our previous work (Sæther et al, 2023), i.e. measures of speed and verbal learning, shared variance with inflammatory-immune markers.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations